Qudiyyatu Wuqu' al-Alfaz al-A'jamiyyat fi al-Qur'an al-Karim - Malibary, Ahmad Akrom (Lajnah Pentashihan Mushaf Al-Qur'an, 2009)
Do the non-Arabic words exist in the QurÃ¢â‚¬â„¢an? There are two opinions of the Muslim scholars regarding this matter. Some reject that there are some non-Arabic words in the QurÃ¢â‚¬â„¢an and some accept it. Each of the group has its own argument. Nevertheless, the strongest argument is that there are some non-Arabic words in the QurÃ¢â‚¬â„¢an, considering that some of those words originated from outside Arabic language but have been absorbed and been treated as the Arabic words. It is not impossible that those words come from theÃ‚Â Semitic language which have been absorbed by some Semitic language branches and the Arabic language is one of the Semitic branches.